The Incidence and Risk Factors of Hip Fracture after Liver Transplantation (LT): A Nationwide Population-Based Study. (26th December 2019) - Chiu, Yung-Cheng; Liao, Pei-Shao; Chou, Yi-Ting; Lin, Cheng-Li; Hung, Chih-Hung; Lin, Che-Chen; Hsu, Chieh-Cheng; Hsu, Horng-Chaung; Huang, Jyun-Ming; Wang, Yang-Yi; Kuo, Shu-Jui
Abstract : Background . Osteoporosis and fragility fracture are the major complications after liver transplantation (LT). The aim of the study was to determine the incidence and risk factors of hip fracture after LT. Methods . We conducted a retrospective population-based cohort study, enrolling the patients receiving LT between January 1999 and December 2010. Control subjects were randomly matched to every recipient by age and sex by 1 : 10 ratios. Results . During the follow-up period, 17 recipients (0.77%) and 70 (0.32%) control subjects suffered from hip fractures. The incident rates (per 10000 person-years) were 21.49 for recipients and 7.52 for controls (adjusted hazard ratio = 2.71; 95% confidence interval = 1.21–6.05). The cumulative incidence of hip fracture was significantly higher among the recipients (p < 0.0001 ). Among the recipients, the subjects aged >65 years at transplantation and with pretransplant steroid use are more susceptible to posttransplant hip fracture. Immunosuppressive agents did not significantly affect the risk of hip fracture among recipients. Conclusions . Liver transplantation is a risk factor for hip fractures. Aged >65 years at transplantation and pretransplant steroid use are risk factors for posttransplant hip fractures among the recipients.